Features of labour contract with separate categories of workers - Гаращенко, Л. П. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article describes the features of employment contracе with some categories of employes in accordancewith the general and special laws of Ukraine.